The Influence of Distance from Health Facility, Family Number at Home and TB History in Starting Treatment of MDR-TB in Medan (Medico Legal Update, 2020)
The national TB Program according to the long-term plan is to prevent and control of drug resistancethrough Management Program of MDR-TB. The objective of the program are reducing morbidity, mortalityand transmission of MDR-TB. Medan is an area with the highest case of MDR-TB in Sumatera UtaraProvince. Until November 2018 MDR-TB case has been confirmed in the city of Medan as many as 324,which has not started the treatment are 61 patients (19%). This research using case-control design andpopulation is all people with MDR-TB in Medan city that recorded in E-TB Manager data. Sample case isthe confirmed MDR-TB person who has not started the treatment as many as 13 people while the control isa confirmed person MDR-TB and willing to start the treatment as many as 31 people. The data is collectedthrough interview using questionnaires and has received approval from the Ethics committee of the Facultyof Nursing University of Sumatera Utara. The data analysis is conducted with the chi-square test and theOR calculation to assess which variables affect the action of beginning MDR-TB treatment. Results showedthat there was no influence of the distance of health facilities (p = 0.188) and family number at home (p =0.507) with the status of starting treatment MDR-TB. There was influence of historical of TB with the statusof starting treatment respondent MDR-TB (p = 0.021)